Lab-scale co-digestion of kitchen waste and brown water for a preliminary performance evaluation of a decentralized waste and wastewater management. (August 2017) - Lavagnolo, Maria Cristina; Girotto, Francesca; Hirata, Osamu; Cossu, Raffaello
Highlights: Co-management of domestic wastewater and organic solid waste was investigated. Anaerobic co-digestion of kitchen waste and brown water led to good methane yields. Co-digestion tests yielded better than single-substrate ones. A small urine concentration in the digested substrate had positive effects. Abstract: An overall interaction is manifested between wastewater and solid waste management schemes. At the Laboratory of Environmental Engineering (LISA) of the University of Padova, Italy, the scientific and technical implications of putting into practice a decentralized waste and wastewater treatment based on the separation of grey water, brown water (BW – faecal matter) and yellow water (YW – urine) are currently undergoing investigation in the Aquanova Project . An additional aim of this concept is the source segregation of kitchen waste (KW) for subsequent anaerobic co-digestion with BW. To determine an optimal mixing ratio and temperature for use in the treatment of KW, BW, and eventually YW, by means of anaerobic digestion, a series of lab-scale batch tests were performed. Organic mixtures of KW and BW performed much better (max. 520 ml CH4 /g VS) in terms of methane yields than the individual substrates alone (max. 220 ml CH4 /g VS). A small concentration of urine proved to have a positive effect on anaerobic digestion performance, possibly due to the presence of micronutrients in YW. When considering high YW concentrations in the anaerobically digested mixtures, no ammonia inhibition was observed until a 30% and 10% YW content was added under mesophilic and thermophilic conditions, respectively.